Concrete mix proportion design method capable of quantifying influence of fibers on workability
By disassembling the fibers on concrete and ease, the mass change caused by fiber water absorption and slurry is calculated, and the concrete mix ratio is adjusted, the complexity problem in the production process of fiber concrete pipe sheets is solved, and the quantitative design and production reliability of mix ratio are achieved.
Patent Information
- Application Number
- CN202411556283.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The prior art lacks methods that can quantify the impact of fiber on concrete and ease, resulting in frequent and ease problems of fiber concrete pipe sheets during production.
By splitting the impact of fiber on concrete and ease into two parts: fiber water absorption and fiber slurry, specific steps are used to calculate the amount of mass changes caused by fiber water absorption and slurry, and adjust the concrete mix ratio to meet the ease requirements.
The quantitative design of the fiber concrete mix ratio is realized, and the ease of the fiber concrete pipe sheet production process is solved, providing a reliable production basis.
Smart Images

Figure CN119517244A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of underground engineering, and in particular relates to a concrete mix design method capable of quantifying the influence of fiber on workability. Background Art
[0002] With the increasing maturity of the application technology of prefabricated segments, the lining structure has higher and higher requirements for the comprehensive quality of the segments themselves. Ordinary reinforced concrete segments have gradually exposed a series of problems, including: excessive steel consumption, low production efficiency, and brittle characteristics that are prone to local damage. Fiber concrete segments have simple construction technology, sufficient bearing capacity, and good crack resistance. They significantly increase the working performance of the segments on the basis of ensuring sufficient bearing capacity. In order to meet the different application environments of the segments, fiber concrete with different dosages is required. 0.5% to 2% volume ratio of fiber is used. The change in dosage will cause a great change in the workability of fiber concrete. In the production process, the situation of "adding more water to the surface and adding more surface to the water" often occurs. The main reason is the lack of research on the influence of fiber dosage on the workability of concrete, and the lack of calculation methods for the mix ratio of high-dosage fiber concrete that can be used for tunnel lining segments. Summary of the invention
[0003] The purpose of the present invention is to solve the above problems and provide a concrete mix design method which can quantify the influence of fiber water absorption and fiber coating on cement slurry, determine the fiber concrete mix ratio and quantify the influence of fiber on workability.
[0004] In order to solve the above technical problems, the technical solution of the present invention is: a concrete mix design method that can quantify the effect of fiber on workability, which divides the effect of fiber on concrete workability into two parts: fiber water absorption and fiber slurry coating, and comprises the following steps:
[0005] S1. Determine the concrete base mix ratio and select raw materials according to requirements and test the various properties of the raw materials;
[0006] S2. Calculate the cement slurry weight;
[0007] S3, determining the water absorption rate of the fiber;
[0008] S4. Calculate the fiber water absorption mass caused by fiber water absorption;
[0009] m 11 =m1f1
[0010] m1 is the fiber mass, m 11 is the fiber water absorption mass, f1 is the fiber water absorption rate;
[0011] S5. Calculate the mass change of the cementitious material caused by the water absorption of the fiber according to S4;
[0012] S6, determining the fiber coating thickness;
[0013] V1=S1D1
[0014] V1 is the volume of fiber coating, S1 is the total surface area of fiber, and D1 is the thickness of fiber coating;
[0015] S7, calculating the mass change of cement slurry caused by fiber coating;
[0016] m2=V1γ
[0017] γ is the cement paste density, V1 is the cement paste volume, and m2 is the cement paste mass change caused by fiber cement paste;
[0018] S8, calculating the mass changes of the cementitious material and the water caused by the fiber coating according to S7;
[0019] S9, according to steps S5 and S8, adding cement, fly ash, water addition amount and actually required fiber amount into the initial mix ratio to obtain the mix ratio after the first adjustment;
[0020] S10, according to the principle that the mix ratio after the first adjustment is equal to the original mix ratio, the mix ratio after the first adjustment is adjusted accordingly to obtain the fiber concrete mix ratio actually used;
[0021] S11. Trial mix is performed according to the mix ratio of step S10. If the workability of the concrete obtained by the trial mix meets the requirements, then the mix ratio meets the requirements. If the workability does not meet the requirements, adjustments are made based on the existing fiber coating thickness, and steps S6 to S11 are continued until the workability of the concrete meets the requirements.
[0022] Furthermore, the raw materials in step S1 include: cement, fly ash, sand, gravel, water, water reducing agent and fiber;
[0023] M1=M 11 +M 12 +M 13 +M 14 +M 15 +M 16 ;
[0024] M1 is the quality of the base concrete mix; 11 is the cement mass, M 12 is the fly ash mass, M 13 is the sand mass, M 14 is the mass of the stone, M 15 is the water quality, M 16 is the mass of water reducer, fiber is 0.
[0025] Furthermore, the calculation method in step S2 is as follows:
[0026]
[0027] γ is the cement paste weight, ρ1 is the cement density, g / cm 3 , K is the water-cement ratio of concrete.
[0028] Furthermore, S3 includes the following sub-steps:
[0029] S31, wipe the fiber clean and weigh W1;
[0030] S32, taking out a certain amount of pure water from a container, and soaking the fiber in the pure water;
[0031] S33, fish out the fiber, absorb the water on the fiber surface with a paper towel or towel, and weigh W2;
[0032] S34, calculating the water absorption rate f1 of the fiber;
[0033]
[0034] Furthermore, the calculation process in step S5 is:
[0035] m 12 =m 11 / K;
[0036]
[0037] m 11 is the water absorption mass of the fiber, m 12 is the mass change of cementitious material caused by fiber water absorption, K is the water-cement ratio of concrete, m 121 : Change in cement mass caused by fiber water absorption, m 122 : Change in fly ash mass caused by fiber water absorption.
[0038] Furthermore, the calculation process in step S8 is:
[0039]
[0040] m 21 is the mass change of cementitious material caused by fiber coating, m 211 is the cement mass change caused by fiber coating, m 212 is the mass change of fly ash caused by fiber slurry coating, m 22 is the change in water mass caused by fiber coating, and K is the water-cement ratio of concrete.
[0041] Furthermore, the mix ratio in step S9 is calculated as follows:
[0042] M 21 =M 11 +m 121 +m 211 ;
[0043] M 22 =M 12 +m 122 +m 212 ;
[0044] M 24 =M 14 +m 11 +m 22 ;
[0045] M2=M 21 +M 22 +M 23 +M 24 +M 25 +M 26 +M7;
[0046] M2 is the concrete mass after the first adjustment of concrete mix ratio, M 21 is the cement mass after the first adjustment of the mix ratio, M 22 M is the fly ash mass after the first adjustment of the mix ratio, 23 Sand quality after the first adjustment of mix ratio, M 24 M is the stone mass after the first adjustment of the mix ratio. 25 M is the water quality after the first adjustment of the mix ratio. 26 M is the mass of water reducer after the first adjustment of mix ratio, and M7 is the mass of fiber after the first adjustment of mix ratio.
[0047] Furthermore, the mix ratio in step S10 is calculated as follows:
[0048]
[0049] n=1~6
[0050] Among them, M 3n M is the quality of concrete material after the second adjustment of mix proportion, 2n The quality of concrete materials after the mix ratio is adjusted for the first time.
[0051] The beneficial effects of the present invention are as follows: the present invention provides a concrete mix design method that can quantify the effect of fiber on workability, quantifies the effect of fiber water absorption and fiber coating on cement slurry, can more reasonably determine the fiber concrete mix ratio, solves the workability problem in the production process of fiber concrete segments, and thus provides a basis for the production of fiber concrete segments. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a flow chart of a concrete mix design method of the present invention that can quantify the effect of fiber on workability; DETAILED DESCRIPTION
[0053] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:
[0054] like Figure 1 As shown, the present invention provides a concrete mix design method that can quantify the effect of fiber on workability, comprising the following steps:
[0055] S1. Determine the concrete base mix ratio and select raw materials according to requirements and test the various properties of the raw materials.
[0056] In this step, according to the designed compressive strength of the segment, the basic mix ratio of concrete is determined in accordance with the "Ordinary Concrete Mix Design Code" (JGJ55) to configure C50 fiber concrete. PO52.5 ordinary Portland cement is selected, and its apparent density is 3100kg / m 3 ; Grade I fly ash, its apparent density is 2450kg / m 3 ; Polycarboxylic acid high-efficiency water reducing agent, with a solid content of 30% and a water reduction rate of 30%; Mixing water is clean tap water; Fine aggregate is graded river sand with a fineness modulus of 2.5-2.7 and an apparent density of 2650kg / m 3 The coarse aggregate is crushed stone with a particle size of 5 to 16 mm and an apparent density of 2700 kg / m 3 The basic matching ratio is shown in the following table.
[0057]
[0058] The raw materials in step S1 include: cement, fly ash, sand, gravel, water, water reducing agent and fiber.
[0059] M1=M 11 +M 12 +M 13 +M 14 +M 15 +M 16 ;
[0060] M1 is the quality of the base concrete mix; 11 is the quality of cement in the basic mix ratio, M 12 is the mass of fly ash in the basic mix ratio, M 13 is the quality of the basic mix sand, M 14 The quality of the stone in the basic mix ratio, M 15 is the quality of basic mix water, M 16 The mass of water reducer for basic mix ratio, fiber is 0.
[0061] Calculate the water-cement ratio:
[0062]
[0063] S2. Calculate the cement slurry density.
[0064] The calculation method in step S2 is as follows:
[0065]
[0066] γ is the cement paste weight, ρ1 is the cement density, g / cm 3 , K is the water-cement ratio of concrete.
[0067] S3. Determine the water absorption rate of the fiber.
[0068] Step S3 includes the following sub-steps:
[0069] S31. Wipe the fiber clean and weigh W1.
[0070] S32. Use a container to take out a certain amount of pure water, and soak the fiber in the pure water.
[0071] S33. Take out the fiber, absorb the water on the surface of the fiber with a paper towel or towel, and weigh W2.
[0072] S34, calculating the water absorption rate f1 of the fiber;
[0073]
[0074] In this embodiment, existing cellulose fibers are selected, with a fiber diameter of 0.016 mm, a length of 2.1 mm, and a density of 1300 kg / m 3 , the fiber volume rate is 0.5%. Based on this, the fiber mass can be calculated to be 5.50kg.
[0075] Surface area of a single fiber: s1 = π × 0.0021 × 0.000016 = 1.055 × 10 -7 m 2
[0076] Volume of a single fiber: v1 = π × 0.0021 × (8 × 10 -6 ) 2 =4.22×10 -13 m 3
[0077] Fiber number: root
[0078] Total fiber surface area: S1 = j1s1 = 1250m 2 .
[0079] S4. Calculate the fiber water absorption mass caused by fiber water absorption.
[0080] m 11 =m1f1
[0081] m1 is the fiber mass, m 11 is the water absorption mass of the fiber, and f1 is the water absorption rate of the fiber.
[0082] In the present invention, step S4 also includes the following sub-steps:
[0083] S41. Wipe the fiber clean and weigh 20g.
[0084] S42. Use a container to take out a certain amount of pure water, and soak the fiber in the pure water.
[0085] S43. Take out the fiber, absorb the water on the surface of the fiber with a paper towel or towel, and weigh 99.6 g.
[0086] S44. Calculate the water absorption rate f1 of the fiber:
[0087]
[0088] W2 is the mass of the fiber after absorbing water, and W1 is the mass before absorbing water.
[0089] S45. Calculate the fiber water absorption mass caused by fiber water absorption:
[0090] m 11 =m1f1=21.89kg.
[0091] S5. Calculate the mass change of the cementitious material caused by the water absorption of the fibers according to S4.
[0092] The calculation process in step S5 is:
[0093] m 12 =m 11 / K=70kg;
[0094]
[0095] m 11 is the mass change of water caused by fiber absorption, m 12 is the mass change of cementitious material caused by fiber water absorption, and K is the water-cement ratio of concrete.
[0096] S6. Determine the fiber coating thickness:
[0097] V1=S1D1
[0098] V1 is the volume of fiber-coated pulp, S1 is the total surface area of fiber, and D1 is the thickness of fiber-coated pulp.
[0099] It is preliminarily determined that the thickness of the pulp coating of a single fiber is 1.5 times the diameter, so the pulp coating thickness is 0.024 mm. The volume of the fiber coating is: V1 = S1D1 = 1250 × 2.4 × 10 -5 =0.03m 3 .
[0100] S7. Calculate the change in cement slurry mass caused by fiber coating.
[0101] m2=V1γ=62kg
[0102] γ is the cement paste density, V1 is the cement paste volume, and m2 is the cement paste mass change caused by fiber coating.
[0103] S8. Calculate the changes in the mass of the cementitious material and the mass of water caused by the fiber coating according to S7.
[0104] The calculation process in step S8 is:
[0105]
[0106] m 21 is the mass change of cementitious material caused by fiber coating, m 211 is the cement mass change caused by fiber coating, m 212 is the mass change of fly ash caused by fiber slurry coating, m 22 is the change in water mass caused by fiber coating, and K is the water-cement ratio of concrete.
[0107] S9. According to steps S5 and S8, cement, fly ash, water addition amount and actually required fiber amount are added to the initial mix ratio to obtain the mix ratio after the first adjustment. The mix ratio is shown in the following table:
[0108]
[0109]
[0110] The mix ratio in step S9 is calculated as follows:
[0111] M 21 =M 11 +m 121 +m 211 ;
[0112] M 22 =M 12 +m 122 +m 212 ;
[0113] M 24 =M 14 +m 11 +m22 ;
[0114] M2=M 21 +M 22 +M 23 +M 24 +M 25 +M 26 +M7;
[0115] M2 is the concrete mass after the first adjustment of concrete mix ratio, M 21 is the cement mass after the first adjustment of the mix ratio, M 22 M is the fly ash mass after the first adjustment of the mix ratio, 23 Sand quality after the first adjustment of mix ratio, M 24 M is the stone mass after the first adjustment of the mix ratio. 25 M is the water quality after the first adjustment of the mix ratio. 26 M is the mass of water reducer after the first adjustment of mix ratio, and M7 is the mass of fiber after the first adjustment of mix ratio.
[0116] S10. According to the principle that the quality of the mix ratio after the first adjustment is equal to that of the original mix ratio, the mix ratio after the first adjustment is adjusted accordingly to obtain the actual fiber concrete mix ratio. The mix ratio is shown in the following table:
[0117]
[0118] The mix ratio in step S10 is calculated as follows:
[0119]
[0120] n=1~6
[0121] Among them, M 3n M is the quality of concrete material after the second adjustment of mix proportion, 2n It is the quality of concrete material after the first adjustment of mix proportion. 31 is the cement mass after the second adjustment of mix proportion, M 32 M is the fly ash mass after the second adjustment of the mix ratio, 33 M is the sand quality after the second adjustment of the mix ratio. 34 M is the stone mass after the second adjustment of the mix ratio. 35 M is the water quality after the second adjustment of the mix ratio. 36 M is the mass of water reducer after the second adjustment of mix ratio, and M7 is the mass of fiber after the second adjustment of mix ratio.
[0122] S11, trial mix according to the mix ratio of step S10, if the workability of the concrete obtained by the trial mix meets the requirements, then the mix ratio meets the requirements. If the workability does not meet the requirements, adjust the existing fiber coating thickness, and continue with steps S6 to S11 until the concrete workability meets the requirements.
[0123] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.
Claims
1. A concrete mix design method capable of quantifying the effect of fiber on workability, characterized in that: The effect of fiber on concrete workability is divided into two parts: fiber water absorption and fiber coating, including the following steps: S1. Determine the concrete base mix ratio and select raw materials according to requirements and test the various properties of the raw materials; S2. Calculate the cement slurry weight; S3, determining the water absorption rate of the fiber; S4. Calculate the fiber water absorption mass caused by fiber water absorption; m 11 =m1f1 m1 is the fiber mass, m 11 is the fiber water absorption mass; f1 is the fiber water absorption rate; S5. Calculate the mass change of the cementitious material caused by the water absorption of the fiber according to S4; S6, determining the fiber pulp coating thickness; V1=S1D1 V1 is the volume of fiber coating, S1 is the total surface area of fiber, and D1 is the thickness of fiber coating; S7, calculating the mass change of cement slurry caused by fiber coating; m2=V1γ γ is the cement paste density, V1 is the cement paste volume, and m2 is the cement paste mass change caused by fiber cement paste; S8, calculating the mass changes of the cementitious material and the water caused by the fiber coating according to S7; S9, according to steps S5 and S8, adding cement, fly ash, water addition amount and actually required fiber amount into the initial mix ratio to obtain the mix ratio after the first adjustment; S10, according to the principle that the mix ratio after the first adjustment is equal to the original mix ratio, the mix ratio after the first adjustment is adjusted accordingly to obtain the fiber concrete mix ratio actually used; S11. Trial mix is performed according to the mix ratio of step S10. If the workability of the concrete obtained by the trial mix meets the requirements, then the mix ratio meets the requirements. If the workability does not meet the requirements, adjustments are made based on the existing fiber coating thickness, and steps S6 to S11 are continued until the workability of the concrete meets the requirements.
2. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The raw materials in step S1 include: cement, fly ash, sand, gravel, water, water reducing agent and fiber; M1=M 11 +M 12 +M 13 +M 14 +M 15 +M 16 ; M1 is the quality of the base concrete mix; 11 is the cement mass, M 12 is the fly ash mass, M 13 is the sand mass, M 14 is the mass of the stone, M 15 is the water quality, M 16 is the mass of water reducer, fiber is 0.
3. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The calculation method in step S2 is as follows: γ is the cement paste weight, ρ1 is the cement density, g / cm 3 , K is the water-cement ratio of concrete.
4. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The S3 comprises the following sub-steps: S31, wipe the fiber clean and weigh W1; S32, taking out a certain amount of pure water from a container, and soaking the fiber in the pure water; S33, fish out the fiber, absorb the water on the fiber surface with a paper towel or towel, and weigh W2; S34, calculating the water absorption rate f1 of the fiber; 5. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The calculation process in step S5 is: m 12 =m 11 / K; m 11 is the water absorption mass of the fiber, m 12 is the mass change of cementitious material caused by fiber water absorption, K is the water-cement ratio of concrete, m 121 : Change in cement mass caused by fiber water absorption, m 122 : Change in fly ash mass caused by fiber water absorption.
6. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The calculation process in step S8 is: m 21 is the mass change of cement paste caused by fiber coating, m 211 is the cement mass change caused by fiber coating, m 212 is the mass change of fly ash caused by fiber slurry coating, m 22 is the change in water mass caused by fiber coating, and K is the water-cement ratio of concrete.
7. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The mix ratio in step S9 is calculated as follows: M 21 =M 11 +m 121 +m 211 ; M 22 =M 12 +m 122 +m 212 ; M 24 =M 14 +m 11 +m 22 ; M2=M 21 +M 22 +M 23 +M 24 +M 25 +M 26 +M7; M2 is the concrete mass after the first adjustment of concrete mix ratio, M 21 is the cement mass after the first adjustment of the mix ratio, M 22 M is the fly ash mass after the first adjustment of the mix ratio, 23 Sand quality after the first adjustment of mix ratio, M 24 M is the stone mass after the first adjustment of the mix ratio. 25 M is the water quality after the first adjustment of the mix ratio. 26 M is the mass of water reducer after the first adjustment of mix ratio, and M7 is the mass of fiber after the first adjustment of mix ratio.
8. A concrete mix design method capable of quantifying the effect of fiber on workability according to claim 1, characterized in that: The mix ratio in step S10 is calculated as follows: n=1~6 Among them, M 3n M is the quality of concrete material after the second adjustment of mix proportion, 2n The quality of concrete materials after the mix ratio is adjusted for the first time.
Citation Information
Patent Citations
Preparation and construction methods of assembled foam concrete slab enclosure wall
CN106747139A
Hybrid steel fiber self-compacting concrete mix proportion secondary design method based on solid phase surface filling layer customization
CN115831269A
Ratio design method for increasing Anti-stretching strength of pavement cement concrete
WO2016078522A1